Financial history of the United States - Cain, James William, 1860-1938.
Typescript (160 pages) of Cain's unpublished work entitled, Financial History of the United States.
Economist and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Economics; Finance; Economists; Educators